Into the Haunted Forest: Reading Anti-Extractivism in Aammton Alias’s The Last Bastion of Ingei - Amran, Rinni (SARE: Southeast Asian Review of English, 2022)
This article posits gothic depictions of the haunted forest as important counter-narratives to extractivist representations of nature in public narratives in Brunei, including government policy and advertising for environmental tourism.The critical discussion will focus on a contemporary Bruneian text, Aammton Alias’sThe Last Bastion of Ingei(2016). Using a localized EcoGothiccritical framework, I argue that the novelreflectsIndigenous ecological beliefs and practices, wherein nature and the supernatural destabilize and undermine anthropocentric ways of knowing and relating to the nonhuman. EcoGothicnarratives can thus be seen as crucial representational models of anti-extractivism that reimagine human-nonhuman relations beyond anthropocentric epistemologies. To this end, I examine the ways in which nature and the supernatural are portrayed and how nonhuman agencies disrupt anthropocentric narration and reading. This article also makes a case for the diversification of local literary and cultural production to effectively reorient public narratives of the environment.